Acute and chronic viruses mediated by an ectoparasite targeting different developmental stages of honeybee (Apis mellifera and Apis cerana) brood - Lin, Zheguang; Zhang, Nan; Wang, Zhi; Zhuang, Mingliang; Wang, Qi; Niu, Defang; Page, Paul; Wang, Kang; Niu, Qingsheng; Ji, Ting (Frontiers in Veterinary Science, 2022)
The health of western honeybee, Apis mellifera, the most crucial pollinator, has been challenged globally over the past decades. An ectoparasitic mite, Varroa destructor, together with the viruses it vectored, is generally regarded as the vital pathogenic agent. Although the poor health status of A. mellifera compared to its eastern counterpart, Apis cerana, has been broadly identified, the underlying mechanism remains poorly understood and comparison between susceptible and resistant hosts will potentially ameliorate this predicament. Here, we investigated the impacts of two widespread viruses—deformed wing virus type A (DWV-A) and Israeli acute paralysis virus (IAPV), mediated by V. destructor mite, on the capped developing honeybee brood, in absence of adult workers, of A. mellifera and A. cerana, with positive and negative controls. Our results demonstrated that the endogenous viruses imposed limited damage to the hosts even if the brood was wounded. In contrast, the exogenous viruses introduced by ectoparasites triggered varied death of the infested brood between host species. Intriguingly, death causes of both honeybee species presented a similar trend: the acute IAPV generally causes morbidity and mortality of late larvae, while the chronic DWV-A typically leads to brood mortality during and after pupation. Notably, the susceptible immature A. cerana individuals, supported by a higher observed mortality and a lower virus tolerance, serve the interests of the colony and foster the overall survival of a resistant honeybee superorganism. These results improve our understanding on the interactions between viruses carried by ectoparasites and their developing hosts, and the novel insight of weak individuals fostering strong colony may promote breeding efforts to mitigate the indefensible colony losses globally.